Engineering Myocardium for Heart Regeneration—Advancements, Considerations, and Future Directions - Jarrell, Dillon K.; Vanderslice, Ethan J.; VeDepo, Mitchell C.; Jacot, Jeffrey G. (Frontiers in Cardiovascular Medicine, 2020)
Heart disease is the leading cause of death in the United States among both adults and infants. In adults, five-year survival after a heart attack is less than 60%, and congenital heart defects are the top killer of liveborn infants. Problematically, the regenerative capacity of the heart is extremely limited, even in newborns. Furthermore, suitable donor hearts for transplant cannot meet the demand and require recipients to use immunosuppressants for life. Tissue engineered myocardium has the potential to replace dead or fibrotic heart tissue in adults and could also be used to permanently repair congenital heart defects in infants. In addition, engineering functional myocardium could facilitate the development of a whole bioartificial heart. Here, we review and compare in vitro and in situ myocardial tissue engineering strategies. In the context of this comparison, we consider three challenges that must be addressed in the engineering of myocardial tissue: recapitulation of myocardial architecture, vascularization of the tissue, and modulation of the immune system. In addition to reviewing and analyzing current progress, we recommend specific strategies for the generation of tissue engineered myocardial patches for heart regeneration and repair.